Tests of Two Models for Valuing Call Options on Stocks with Dividends - STERK, WILLIAM (Journal of Finance, 1982)
ABSTRACT Roll has recently formulated an option pricing model which allows dividend payments on the underlying stock. This paper compares the performance of the exact Roll model with a modified, but inexact, Black‐Scholes model. The results indicate that the Roll model prices are significantly closer to actual market prices.